The The Correlation between Tuberculous Lymphadenitis and Nutritional Status in Children - Shodikin, Muhammad Ali; Sutejo, Ika Rahmawati; Putri, Yasmin Auralia (Journal of Health Sciences, 2022)
Tuberculous lymphadenitis may cause weight loss and lead to malnutrition in children. This study analyzes the correlation between tuberculous lymphadenitis and nutritional status in children. It was an analytic observational study with a cross-sectional design. The population was pediatric patients under 18 years old with lymphadenitis, outpatient and inpatient admitted from January 2018 to December 2020 in dr. Soebandi public hospital, Jember, Indonesia. The samples were 76 respondents with total sampling. There were 52 tuberculosis lymphadenitis patients in the case group, while 24 were non- tuberculosis in the control group. The body weight data was from the medical record when the first diagnosis of lymphadenitis. Instruments were weight-for-age z-score curves (WHO, 2007) for under 60 months old children, while CDC Growth Charts 2000 for more than five-year-old children. Then, data analysis used the Chi-square test. Mostly, tuberculous lymphadenitis patients were girls (65.4%), 12-17 years old (67.3%), not underweight (61.5%), and lived in rural areas (73%). Furthermore, all of them were given isoniazid, rifampicin, and pyrazinamide. In addition, 100% of them had successful treatment. Meanwhile, most of the non-tuberculous lymphadenitis patients were boys (54.2%), 6-11 years old (58.3%), lived in the rural areas (79%), and were not underweight (66.7%). Treatment of the non-tuberculous lymphadenitis group consisted of antibiotics, analgesics, vitamins, and symptomatic medicine. The Chi-square test results obtained p=0.667 (p>0.05). In conclusion, tuberculosis lymphadenitis in the early incubation period